Genome variations of Puumala virus strains circulating in Nizhnekamsky and Tukaevsky districts of the Republic of Tatarstan - E. Kabwe; Y.N. Davidyuk; S.P. Morzunov (Учёные записки Казанского университета: Серия Естественные науки)
Puumala virus (PUUV), which causes hemorrhagic fever with renal syndrome (HFRS), is endemic in Russia, including the Republic of Tatarstan (RT). Although hundreds of HFRS cases are recorded in RT annually, little is known about the genetic diversity of PUUV in Tatarstan. For this study, partial PUUV sequences of the S and M genome segments were obtained from bank vole populations in Tukayevsky and Nizhnekamsky districts. The genetic diversity among newly identified PUUV isolates was in the range of 0.0–3.3% for both S and M genome segments, with these isolates displaying from 5.1% to 7.8% of nucleotide sequence differences from the strains previously identified in Russia. All the recovered PUUV genome sequences phylogenetically clustered with the known PUUV strains of the previously defined Russian (RUS) genetic lineage and clearly differed from other strains circulating in the RT. It was found that the genome composition of PUUV/Nizhnekamsky/MG_134/2015 strain is likely to be a result of the intra-lineage recombination or genetic reassortment of two distinct PUUV strains.